Credit Allocation and Credit Interest Affect Small Business income. in the Non-Governmental Organization KIF (Kaebauk Investimentu Finansas) Dili, Timor-Leste - Amaral, Adolmando S. Amaral; Costa, Francisco da; Viegas, Fortunata Ximenes (Yayasan Sinergi Kawula Muda, 2024)
This study aims to determine the effect of credit allocation and credit interest on small business income in Dili, Timor-Leste. The type of research used in this scientific work is a type of survey conducted by the KIF Organization Agent on credit customers before and after receiving credit, while the population is used as the number of customers and the sample used is 55 credit customers to represent credit survey data in Dili City. The method of using samples in this study is probability sampling, namely sampling quotations (Census). The analysis material used in this scientific work is multiple linear regression. The results of this study are interpreted as changes in poverty levels and levels of difficulty, so from 55 respondents, namely changes from poor to non-poor. The results of this study indicate that: (1) The SPSS output score shows the T value of the credit allocation variable (X1) of 2.696 with a significance level of 0.000 below 5%, the T value of 2.696> 2.006, the t table confidence level is 95% and the standard error is 5%, with the alternative hypothesis (Ha) being accepted. The results of the analysis between the level of credit allocation (X1) and credit interest (X2) are valid or adequate as a measure of small business income (Y). The results of the statistical test show that there is a difference in income before and after receiving credit for positive credit customers. These results also indicate a positive and significant correlation and influence simultaneously between the credit allocation and credit interest variables on small business income.